Deletion of metal transporter Zip14 reduces major histocompatibility complex II expression in murine small intestinal epithelial cells - Felix R. Jimenez-Rondan; Courtney H. Ruggiero; Alberto Riva; Fahong Yu; Lauren S. Stafford; Tyler R. Cross; Joseph Larkin; Robert J. Cousins (Proceedings of the National Academy of Sciences, 2025)
Documented worldwide, impaired immunity is a cardinal signature resulting from loss of dietary zinc, an essential micronutrient. A steady supply of zinc to meet cellular requirements is regulated by an array of zinc transporters. Deletion of the transporter Zip14 (Slc39a14) in mice produced intestinal inflammation. Elevated fecal lipocalin-2, calprotectin, IgG levels, and dysbiosis support the inflammatory phenotype. Here, we show through RNA-sequencing, using purified intestinal epithelial cells (IECs), that Zip14 deletion produces markedly reduced expression of major histocompatibility complex class II (MHCII) molecules and the master MHCII transactivator ( Ciita ). qPCR, western analysis, and immunohistochemistry confirmed loss of MHCII. Spectrofluorimetry with zinc probe FluoZin-3 showed reduced labile zinc in IECs from knockout mice. Chromatin immunoprecipitation assays, using Ciita antibody and IEC chromatin, suggest decreased transcription accounts for depressed expression of specific MHCII genes. Assay for Transposase-Accessible Chromatin (ATAC) sequencing (ATAC-seq) demonstrated that H2-Aa , H2-Ab1 and other MHCII genes result from chromatin remodeling yielding closed chromatin at regulatory regions of these genes. In agreement, ATAC-seq showed peak density of the chromosomal regulatory region of Ciita is consistent with down regulation of specific MHCII genes in IECs with Zip14 loss. Finally, dietary zinc supplementation of knockout mice and zinc supplementation of intestinal organoids with Zip14 deletion restored transcript levels. Taken together, our data suggest that cellular zinc delivery, via Zip14, is necessary for proper chromatin occupancy, required for normal MHCII expression and effective immune functions, and to preclude inflammatory disorders of the small intestine.